АНАЛІЗ СТАНУ ІНДИВІДУАЛІЗАЦІЇ ПРОФЕСІЙНО ОРІЄНТОВАНОГО НАВЧАННЯ ІНОЗЕМНИХ МОВ СТУДЕНТІВ ІІЕМОВНИХ СПЕЦІАЛЬНОСТЕЙ У ВИЩИХ ПЕДАГОГІЧНИХ ЗАКЛАДАХ (Педагогіка вищої та середньої школи, 2022)
The article is devoted to analyzing of individualization level of students of non linguistic specialities in pedagogical high schools. The author is describing the up-to-date condition of educational programs and results of students questioning.